2015
DOI: 10.1109/tvcg.2015.2396064
|View full text |Cite
|
Sign up to set email alerts
|

Fast Edge-Aware Processing via First Order Proximal Approximation

Abstract: Abstract-We present a new framework for fast edge-aware processing of images and videos. The proposed smoothing method is based on an optimization formulation with a non-convex sparse regularization for a better smoothing behavior near strong edges. We develop mathematical tools based on first order approximation of proximal operators to accelerate the proposed method while maintaining high-quality smoothing. The first order approximation is used to estimate a solution of the proximal form in a half-quadratic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…in Section 4.4 in detail. While Badri et al [29] used a similar nonconvex objective function for image smoothing, our model provides a more generalized objective for joint image filtering. Shen et al [30] used the common structure in input and guidance images, but the local filtering formulation of the filter introduces halo artifacts and limits the applicability.…”
Section: Image Filtering and Joint Image Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…in Section 4.4 in detail. While Badri et al [29] used a similar nonconvex objective function for image smoothing, our model provides a more generalized objective for joint image filtering. Shen et al [30] used the common structure in input and guidance images, but the local filtering formulation of the filter introduces halo artifacts and limits the applicability.…”
Section: Image Filtering and Joint Image Filteringmentioning
confidence: 99%
“…4. The SD filter of (11) applies the very popular WLS filter [23] iteratively with a fixed input image, allowing us to use many acceleration techniques for WLS filtering [29], [55]. When using MEX implementation of the fast WLS algorithm in [55], we obtain the filtering result with 0.1 seconds for the same image size.…”
Section: Runtimementioning
confidence: 99%
“…All the solvers are implemented in MATLAB. For the PCG solver, we adopt the MATLAB build-in incomplete Cholesky factorization preconditioner which is faster than the one presented in [Krishnan et al 2013] as reported by Badri et al [Badri et al 2013[Badri et al , 2015. For both of the intensity domain solvers, the time of constructing the Laplacian matrix is also included in the measured time.…”
Section: Iterative Least Squaresmentioning
confidence: 99%
“…Unfortunately, this inverse function cannot be evaluated directly for the l p -norm. However, a solution can be approximated via a first-order Taylor expansion [39] :…”
Section: Appendix L P -Shrinkage Solutionmentioning
confidence: 99%